BILIARY ASCARIASIS IN CHILDREN - ALAM, JAVED; WAZIR, MEHAR DIL KHAN; MUHAMMAD, ZARDAD (Journal of Ayub Medical College Abbottabad, 2001)
Background: Ascariasis is very common in this part of the world. Biliary Ascariasis is rare but is the commonest extra-intestinal complication. Methods: This study was conducted at Ayub leaching Hospital, Abbottabad, a tertiary’ care hospital. Five cases of biliary Ascariasis were studied from December 1999 to January 2001. History of passage of worms in stool or vomiting and abdominal pain was taken. After clinical evaluation. Stool Examination, Serum amylase, LFTs, and complete blood picture (CP) were done. Ultrasound abdomen was done as a basic tool for diagnosis. All cases were given Piperazine. Spasmolytics were also given to relax sphincter of oddi to release the worms. Surgical opinions were also taken for each case. Results: About 80% Children were above 10 years of age. One case was 1 % years old. Most common symptom was right upper quadrant abdominal pain. Previous history of passage of worms in stool and vomitus was also present. Two children developed complications of Biliary Ascariasis i.e., Cholecystitis and Portal empyema and responded to antibiotics. All children became symptom free in about 48 hours of treatment. Ultrasound was found to be a reliable, non-invasive, and quick tool for diagnosis and follow up.